Edukasi Hukum tentang Hak-Hak Anak dalam Hukum Keluarga Islam: Pengembangan Modul dan Pelatihan bagi Guru dan Orang Tua - Sugeng Aminudin; Faris Maulana Akbar; Siti Salma As-Shiddiqah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study aims to develop a legal education module that focuses on children's rights in Islamic family law, as well as implementing training for teachers and parents. The main objective of this study is to improve understanding of children's rights in the context of Islamic law, so that it can be applied in family and educational environments. The research method used is the Research and Development (R&D) method with a qualitative approach. Data were collected through interviews, observations, and questionnaires to teachers, parents, and Islamic legal experts. Module development was carried out through the stages of design, expert validation, revision, and field trials. Training was designed based on the developed module and involved the active participation of teachers and parents. In academic debates, this study refers to the growing discussion around children's rights in Islamic family law, which often clash with diverse traditional interpretations in various Muslim-majority countries. Some researchers argue that children's rights are often under-prioritized in everyday practice, while others argue that Islamic law provides a sufficient framework to protect children's rights if applied properly. The results of the study indicate that this legal education module is effective in improving teachers' and parents' understanding of children's rights in Islamic families. The module-based training successfully increased the active involvement and awareness of participants about the importance of protecting children's rights. The module also has the potential to be applied more widely in various educational and community contexts.